1995
DOI: 10.1080/09670269500650991
|View full text |Cite
|
Sign up to set email alerts
|

Systematics and distribution of freshwaterAudouinella(Acrochaetiaceae, Rhodophyta) in Brazil

Abstract: Forty-five Brazilian populations of freshwater Audouinella were analysed using multivariate morphometrics. These populations were statistically related to seven type specimens. Five species are recognised on the basis of qualitative (plant colour and size, basal system type and branch angle) and quantitative (length and diameter of vegetative cells and monosporangia) characters. A. hermannii (syn. A. violacea) is characterised by a reddish colour, an irregular prostrate basal system, open branch angles (~ 25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 6 publications
(2 reference statements)
0
12
0
Order By: Relevance
“…Because the Spirogyra samples were not reproductive and therefore could not be identified to species it is difficult to ascertain if this is a single cosmopolitan taxon or a species complex. Audouinella pygmaea is a common inhabitant of streams in the coastal plains and tropical North America, as well as southeastern Brazil in South America (Necchi et al 1993, N ecchi andZucchi 1995). Phornzidium retzii has been noted to be the most common macroalga in North American streams as a whole, occurring in 32% of those in tropical regions (Sheath and Cole 1992).…”
Section: Leptolyngbya Angustissima Bluish Noncapitate Wlbranchedmentioning
confidence: 99%
“…Because the Spirogyra samples were not reproductive and therefore could not be identified to species it is difficult to ascertain if this is a single cosmopolitan taxon or a species complex. Audouinella pygmaea is a common inhabitant of streams in the coastal plains and tropical North America, as well as southeastern Brazil in South America (Necchi et al 1993, N ecchi andZucchi 1995). Phornzidium retzii has been noted to be the most common macroalga in North American streams as a whole, occurring in 32% of those in tropical regions (Sheath and Cole 1992).…”
Section: Leptolyngbya Angustissima Bluish Noncapitate Wlbranchedmentioning
confidence: 99%
“…Like B. investiens , O. meiospora is also an endophyte of freshwater rhodophytes, but from the Southern Hemisphere: originally described from New Zealand (Skuja , as B. meiospora ) and reported more recently from South America as endophytes of Compsopogon caeruleus and as the chantransia stage of Batrachospermum macrosporum (Necchi and Zucchi , although these reports from Brazil should be re‐examined in light of our findings here). The investigation and publication of this taxon from North Island of New Zealand was a Second World War project for Skuja, some of his final work in Latvia before fleeing to Sweden in 1944 (Entwisle ).…”
Section: Resultsmentioning
confidence: 52%
“…Distribution: Recorded as endophyte of Batrachospermales in streams in Wilsons Promontory ( N. wattsii ) and Yarra River basin ( N. lindaueri , N. nodosus and N. wattsii ) in Victoria; Lamonds Creek in Barren Grounds Nature Reserve and Little Murray River near Dorrigo ( N. theaquus ) in New South Wales (Skinner and Entwisle ); and within N. lindeaueri from Bay of Islands of the North Island, New Zealand (Skuja ). Records from Brazil (Necchi and Zucchi ) require confirmation in light of this study.…”
Section: Resultsmentioning
confidence: 84%
“…The New South Wales material cited above has a general morphology similar to Brazilian material described by Necchi and Zucchi (1995), and the dimensions similar to both the type and the North American material of Necchi et al (1993a). Harper and Saunders (1998) using a Victorian collection comparable with the New South Wales material and sequenced by Vis et al (1998), showed 100% complementarity in rbcL gene sequences between Australian and North American material.…”
Section: Notesmentioning
confidence: 60%
“…The vegetative cells of A. scopulata are much thicker than A. tenella (12-15 µm cf. 4-6 µm; see Necchi and Zucchi 1995), and tetrasporic material has yet to be found. The process of sexual reproduction appears to be similar to the pattern described for Audouinella hermannii (as Rhodochorton violaceum) by Drew (1935) and Necchi et al (1993a).…”
Section: Audouinella Scopulata Skinner and Entwisle Sp Novmentioning
confidence: 99%